Urinary volatile Organic compounds in non-alcoholic fatty liver disease (NAFLD), type two diabetes mellitus (T2DM) and NAFLD-T2DM coexistence - Cozzolino, Rosaria; De Giulio, Beatrice; Martignetti, A; Forte, G; Dallio, M; Romeo, M; Scognamiglio, F; Ventriglia, L; Stocchero, M; Federico, A (Metabolomics, 2022)
Introduction Accumulating evidence have shown a significant correlation between urinary volatile organic compounds (VOCs) profile and the manifestation of several physiological and pathological states, including liver diseases. Previous studies have investigated the urinary metabolic signature as a non-invasive tool for the early discrimination between non-alcoholic fatty liver (NAFL) and non-alcoholic steatohepatitis (NASH), which nowadays represents one of the most important challenges in this context, feasible only by carrying out liver biopsy. Objectives The aim of the study was to investigate the differences in the urinary VOCs profiles of non-alcoholic fatty liver disease (NAFLD) patients, diabetes mellitus (T2DM) subjects and NAFLD/T2DM patients. Methods Headspace solid-phase microextraction (HS-SPME) coupled with gas chromatography–mass spectrometry (GC-MS) was applied to profile the urinary VOCs. Urine samples were analysed both under acid and alkaline conditions, to obtain a range of urinary volatiles with different physicochemical properties. Results Urinary VOCs profiles of 13 NAFLD patients, 13 T2DM subjects and 13 NAFLD/T2DM patients were investigated by multivariate and univariate data analysis techniques which allowed to identify 21 volatiles under alkaline conditions able to describe the NAFLD/T2DM group concerning the other two groups. Conclusion Our results suggest that VOCs signatures can improve the knowledge of the pathological condition where NAFLD coexists with T2DM and discovering new features that are not simply the sum of the two diseases. These preliminary findings may be considered as hypothesis-generating, to be clearly confirmed by larger prospective investigations.